2016
DOI: 10.1111/jocn.13434
|View full text |Cite
|
Sign up to set email alerts
|

‘Feeling someone is there for you’ – experiences of women with vulvar neoplasia with care delivered by an Advanced Practice Nurse

Abstract: Addressing psychosocial needs in caring for women with vulvar neoplasia must be given greater attention in clinical practice. Further, continuous nursing support delivered by an Advanced Practice Nurse beyond the acute treatment phase can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 32 publications
1
24
0
5
Order By: Relevance
“…Therefore, it can be assumed that a longer counselling time contributes to resolving disease-related uncertainties and developing effective problem-solving strategies [16] and supports to cope successfully with symptomrelated distress. This assumption is confirmed by a qualitative study, where women reported that they felt safe and secure because they were more confident after the APN actively took time to talk to them and discuss their concerns [32].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Therefore, it can be assumed that a longer counselling time contributes to resolving disease-related uncertainties and developing effective problem-solving strategies [16] and supports to cope successfully with symptomrelated distress. This assumption is confirmed by a qualitative study, where women reported that they felt safe and secure because they were more confident after the APN actively took time to talk to them and discuss their concerns [32].…”
Section: Discussionmentioning
confidence: 72%
“…Qualitative studies have indicated that social support, especially for patients with taboo diseases, such as vulvar neoplasia, is important to successfully cope with the situation. It allows talking about the experience and contributes to reduced stress and higher emotional well-being [32,36]. Social support can be from different sources, such as family, friends or other important persons [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, medical staff can help patients with cancer adapt to such "disease tasks" by supporting them in adapting to the diseases and treatment methods. Nursing intervention from advanced practice nurses who are recognized by patients as care providers who know them best and are trustworthy [26] will be especially helpful.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to reduced stress and higher emotional well-being [29]. Qualitative studies demonstrate that women with vulvar neoplasia are ashamed of talking about their disease and they feel alone [8,30]. However, Rüegsegger et.…”
Section: Insert Table 3 Discussionmentioning
confidence: 99%